Morbidity related to major lung thoracoscopic resections in children - Sara Ugolini; Lorenzo Tofani; Elisa Zolpi; Louise Montalva; Cosimo Lotti; Antonino Morabito; Fabio Chiarenza; Arnaud Bonnard (PAGEPress Publications, 2024)
In pediatric thoracic surgery, reported predictors for increased risk are symptoms and active/previous infections (RAP). We investigated the adverse events related to Video-Assisted Thoracic Surgery (VATS) in pediatric patients when considering RAP predictors. A retrospective analysis of pediatric VATS major lung resections in 2008-2021 was conducted at three institutions. We employed the pediatric surgical risk calculator to define patients' preoperative predicted risk (PredR). Postoperative complications were classified according to the Thoracic Morbidity & Mortality (TM&M) system. The observed TM&M rate (ObsR) and the PredR were compared. A subgroup analysis by RAP predictors was conducted. 37 patients (54% female) were included. Mean age and weight were 5.8 years and 22.8 kg. 56.7% had respiratory symptoms, 38.9% active infection and 59.5% history of infections (RAP subpopulations). VATS procedures were lobectomy (n=32), segmentectomy (n=3), bilobectomy (n=1) and pneumonectomy (n=1). The conversion rate was 5.4%. The mean PredR was of 4.43% (±1.8) and the overall ObsR was 45.94% with a median severity of II (I-III). This difference was significant and a higher PredR was not associated with complications development. PredR does not show association among the RAP vs non-RAP group. ObsR showed positive association with RAP, even if it reached statistical significance only for "respiratory symptoms" risk factor. ObsR reflected the number of bronchiectasis patients in our series (n=9), aligning with the hypothesis of "earlier and safer surgery". The risk calculator underestimates VATS morbidity. Multicentre studies will clarify the correlation between inflammation and surgical adverse events.